2021
DOI: 10.1007/s10815-021-02105-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ovarian pentraxin 3 in polycystic ovary syndrome

Abstract: Purpose Pentraxin 3 (PTX3) plays a crucial role in cumulus expansion and fertilization. The ovarian PTX3 level in polycystic ovary syndrome (PCOS) remains uncertain. In the present study, we investigated the follicular PTX3 levels and found the influence of reproductive hormones on ovarian PTX3 concentration. Methods This study was based on 204 healthy-weight women (102 PCOS and 102 normal ovulating subjects) undergoing in vitro fertilization (IVF). Follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…With regards to PTX3, recent research demonstrated that PTX3 in circulation is associated with PCOS (64, 65) but its role is so far inconclusive. There was a significantly higher level in the PCOS women than in control which supports the low-grade inflammatory state in PCOS (32). In contrast, another study found no significant difference in the level of PTX3 between cumulus cells in the MII and MI/GV stage, however, there were significant differences in PTX3 level between cumulus cells isolated from mature oocytes that formed two normal pronuclei or multi-pronuclei after fertilization (14).…”
Section: Genes Related To Cumulus Expansion and Apoptosismentioning
confidence: 73%
See 1 more Smart Citation
“…With regards to PTX3, recent research demonstrated that PTX3 in circulation is associated with PCOS (64, 65) but its role is so far inconclusive. There was a significantly higher level in the PCOS women than in control which supports the low-grade inflammatory state in PCOS (32). In contrast, another study found no significant difference in the level of PTX3 between cumulus cells in the MII and MI/GV stage, however, there were significant differences in PTX3 level between cumulus cells isolated from mature oocytes that formed two normal pronuclei or multi-pronuclei after fertilization (14).…”
Section: Genes Related To Cumulus Expansion and Apoptosismentioning
confidence: 73%
“…Besides the HAS2 gene, PTX3 also has a clear role in cumulus expansion. This molecule co-localizes with hyaluronic acid throughout the cumulus matrix with the help of tumor necrosis factor a-induced protein 6 (TNFAIP6) and is essential for in vivo fertilization (32). Inactivation of this gene reduced the ability of oocytes to fertilize, by disrupting the structural integrity of the cumulus oocytes complex.…”
Section: Genes Related To Cumulus Expansion and Apoptosismentioning
confidence: 99%
“…In addition, whether the PTX3 levels are correlated with insulin resistance status and hyperandrogenemia in PCOS patients remains to be elucidated. Pan et al found that women with PCOS had higher PTX3 levels, indicating that the relatively low in ammatory status in PCOS patients with a dysfunctional pituitary gland and ovarian hyperandrogenism (35).However, to our knowledge, only few studies on PTX3 levels in follicular uid samples and granulosa cells obtained from PCOS patients have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…macrophages, dendritic cells, and CD8 + T cells) in the ovary and endometrium of PCOS women (74,75), which possibly compromise ovarian function, normal implantation, and endometrial health in the long run. For example, pentraxin-3 (PTX3), a crucial humoral innate immunity component secreted by macrophages, which stands out as a structural constituent of the cumulus oophorus extracellular matrix essential for female fertility, was reported abnormally high both in plasma and ovary in PCOS women (76)(77)(78). And higher PTX3 is associated with hyperandrogenism (79), which might perturb interactions of the sperm with the matrix during in vivo fertilization (80).…”
Section: Impaired Fertilitymentioning
confidence: 99%